Effect of charge compensators A+ (A = Li, Na and K) on luminescence enhancement of Ca3Sr3(PO4)4:Sm3+ orange-red phosphors. Issue 16 (November 2018) - Fan, Jun; Zhang, Wentao; Dai, Siyi; Yan, Guilin; Deng, Miao; Qiu, Kehui
Abstract: A novel Ca3 Sr3 (PO4 )4 :Sm 3+ orange-red phosphor was synthesized by a high temperature solid-state reaction, and its luminescence was characterized indepth. The results show that Ca3 Sr3 (PO4 )4 :Sm 3+ phosphor could be effectively excited by near-ultraviolet light of 405 nm. Three sharp emission peaks were observed at 566 nm, 603 nm and 650 nm, corresponding to the 4 G5/2 → 6 H5/2, 4 G5/2 → 6 H7/2 ) and 4 G5/2 → 6 H9/2 ) transitions, respectively. With a Sm 3+ ion concentration at x = 0.06, the luminescence intensity reached a maximum and then concentration quenching occurred. In addition, the effect of adding a charge compensator A + (A = Li, Na and K) on the luminescence properties of Ca3 Sr3 (PO4 )4 :Sm 3+ was investigated. The luminescence intensity was improved effectively with alkali metal ions co-doping. Among these alkali metal ions, Li + ions were most effective. Thus, Ca3 Sr3 (PO4 )4 :Sm 3+, Li + orange-red phosphor can be used as a promising phosphor for application in near-ultraviolet-excited white light-emitting diodes.